In Sacco Rumen Degradation of Ensiled Maize Cobs Treated with Non Protein Nitrogen (Urea) - Babangida, L.; Nasir, A.; Muhammad, I. R.; Mansur, S. J.; Audu, R.; Bature, N.; Gumel, I. A.; Tijjani, A.; Suleiman, M. R. (Nigerian Journal of Animal Science and Technology (NJAST), 2022)
In sacco ruminal degradability is an important measurement in the determination of the nutritive value of feedstuffs. Two experiments were conducted to evaluate the effect of non-protein nitrogen (urea) on the in sacco degradability of maize cobs ensiled for three (3), five (5) and seven (7) weeks. The first experiment was to evaluate the effect of non-protein nitrogen (urea) on the quality of maize cob silage. The experiment was laid out in a completely randomized design (CRD) with three ensiling periods and three replications. The second experiment was to determine the effect of the first experiment on in sacco degradability of treated maize cob silage. In sacco studies were conducted in three fistulated kano brown bucks. Nylon bags containing 4 g of feed sample were inserted in triplicate at each time point in the ventral rumen of each buck for 8, 12, 18, 24, 36, and 48 hrs. The data of rumen feed degradation characteristics were fitted to the equation P = a+b (1-e-ct) and effective degradability were calculated using a theoretical rumen out flow rate of k= 0.02/hr, k = 0.05/hr and k= 0.08/hr. Results obtained revealed that physical properties of treated maize cob silage were improved with increasing ensiling period from three to seven weeks. Desirable pH (3.22-3.80) was obtained in all silages; while colour and aroma improved significantly (p<0.05) at the 7th week ensiling period. Silage protein content (10.78%) was significantly (p<0.05) higher at the 7th week while crude fibre decreased significantly (p<0.05) at the 7th week of ensiling. The dry matter disappearance and degradability values were greatest at the 7th week while effective degradability increase with the increasing ensiling times at different outflow rates. Therefore, it was concluded that the physical, nutritional and degradation characteristics of ensiled urea treated maize cobs improved with increase in ensiling period up to the 7th week.